TRADISI NGUTANG DI PASAR TRADISIONAL (Studi di Pasar Tradisional Gunungpati) - Baidhowi, Baidhowi (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
The traditional market is an important place in the life of the Java community. For society, the market not only as a meeting place for sellers and buyers, but also as a forum for social interaction and representation of traditional values indicated by market actors (traders, buyers and banks thithil / renten). The actors in offering their goods prioritizing personal approach and familial / social networking. Established market atmosphere is not just a formal relationship of buying and selling between sellers and buyers, but more than that, that they greet each other and chat. So for the people shopping at a crowded market and not too clean it into the enjoyment of life of its own. Capital constraints for traders to be one of a phenomenon that is addressed to